Effect of electric load impedances on the performance of sandwich piezoelectric transducers - Lin, Shuyu (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2004)
Based on the electromechanical equivalent circuit, the sandwich piezoelectric transducer with adjustable resonance frequency is studied. The underlying theory of frequency adjustment is its piezoelectric effect. In this paper, the influence of electric load impedance (including electric resistance, electric inductance, and electric capacitance) on the resonance frequency, the antiresonance frequency, and the effective electromechanical coupling coefficient is analyzed theoretically and experimentally. It is demonstrated that the electric load impedance can change the resonance frequency, the antiresonance frequency, and the effective electromechanical coupling coefficient. When the electric load resistance is increased, the resonance frequency and the antiresonance frequency are increased; the effective electromechanical coupling coefficient has a maximum value when the electric load resistance changes. When the electric load resistance becomes large, the effect of the electric load resistance on the effective electromechanical coupling coefficient is negligible. When the electric load inductance is increased, the resonance frequency and the antiresonance frequency are decreased, whereas the effective electromechanical coupling coefficient is increased. When the electric load capacitance is increased, the resonance frequency, the antiresonance frequency, and the effective electromechanical coupling coefficient are all decreased. It should be noted that when the electric load impedance becomes large, the effect of the electric load impedance on the resonance frequency, the antiresonance frequency, and the effective electromechanical coupling coefficient of a sandwich piezoelectric transducer becomes negligible